IMachining technology analysis for contour milling - Y. V. Petrakov; А. V. Myhovych (Mechanics and Advanced Technologies, 2020)
Recognizing the practical need to control the cutting process, leading firms in the high-tech market began to offer software products that, in the automatic mode, were said to be able to calculate the optimal cutting mode. Currently, the most advanced technology is called iMachining, which means intelligent Machining. The article presents an analysis of the control, automatically designed in the iMachining Solid CAM module, for machining a test part, the contour of which is formed by two straight circular arcs of a circle. It is shown that when designing control, geometric criteria are used that are associated with the path of shaping, so stabilization of the cutting process is not achieved. A control design method is proposed based on the results of simulation the Material Removal Rate (MRR), which allows stabilizing the cutting process.